The Dynamics of the Legal Status of Administrative Bodies in the Time of Reform: A Socio-Legal Perspective on Conditions and Principles - Vdovichen, Vitalii; et al. (European Journal of Social Science Education and Research, 2026)
In the context of contemporary socio-political transformations, including the implementation of public administration reform, decentralization, and the digitalization of governance, the issue of updating the legal status of administrative bodies has become increasingly significant. Growing public expectations and the crisis of institutional legitimacy further intensify the need to reconsider the legal and organizational foundations of public authorities. This study aims to determine the legal basis of the status of administrative bodies and to analyze the key prerequisites necessary for effective reform of the public administration system. Particular attention is given to political, legal, institutional, human, social, and technological determinants that influence the capacity of the state’s institutional framework to implement effective changes. Public authorities are examined as subjects of public administration whose legal status evolves in response to external challenges. The research methodology includes logical-semantic, formal-legal, structural-functional, and comparative methods. The study proposes a comprehensive definition of the legal status of an administrative body that integrates rights and obligations, institutional features, powers, and responsibilities. It distinguishes between general legal status, determined by the organizational and legal form, and a special administrative-legal status. The research also identifies key principles for successful reform, such as structural adaptability, system integration, participation, legal legitimacy, and personnel stability. The findings may contribute to developing an improved regulatory model of administrative bodies aimed at strengthening transparency and efficiency in democratic public administration.